The influence of occupational safety and health on work engagement - Andreine, Refrelza El Nisaa; Kusmaryani, Rosita Endang; Purwaniningtyas, Dyah Ayu (Faculty of Psychology, Universitas Negeri Yogyakarta, 2022)
This study is conducted based on the phenomenon of low work engagement in companies, the possible one is due to lack of application Occupational Safety and Health (OSH). This paper aims to determine the effect of Occupational Safety and Health (OSH) on work engagement on employees. This research uses a quantitative approach to the type of ex post facto.The sampling technique in this research is purposive sampling and the samples in this research is employee of PT Telkom Access Pugeran Yogyakarta branch, with the scale of 96 employees, 67 male employees and 29 female employees. The instruments of this research used two psychological scales, namely OSH scale and work engagement scale. Analyzed data by using descriptive analysis and simple linear regression analysis. The results of the regression analysis score are 0,000 < 0,05, it can be concluded that there is a positive influence of Occupational Safety and Health (OSH) on work engagement. The coefficient determination or R Square is 0,498 or 49,8%, meaning that 49,8% of employees work engagement is influenced by OSH, while the remaining 50,2% is influenced by other factors not examined in this study.